Pilot study to assess the influence of an enhanced medication plan on patient knowledge at hospital discharge - Send, Alexander Francesco Josef; Schwab, Michael; Gauss, Annika; Rudofsky, Gottfried; Haefeli, Walter E.; Seidling, Hanna (European journal of clinical pharmacology, 2014)
This study assessed the effect of providing an enhanced medication plan (EMP) to patients during patient-physician conversation at hospital discharge and evaluated its immediate impact on patient knowledge on pharmacotherapy.
Gesehen am 09.07.2020